Performance of the Sharpe Portfolio Selection Model: A Comparison - Frankfurter, George M.; Phillips, Herbert E.; Seagle, John P. (Journal of Financial and Quantitative Analysis, 1976)
George M. Frankfurter, Herbert E. Phillips, John P. Seagle, Performance of the Sharpe Portfolio Selection Model: A Comparison, The Journal of Financial and Quantitative Analysis, Vol. 11, No. 2 (Jun., 1976), pp. 195-204